A comparative study of subjective well-being, interpersonal relationship and love forgiveness among Chinese college students before and after the COVID-19 epidemic - Cheng, Tianyi; Qiyi, Lin; Fu, Hong (Frontiers in Psychology, 2023)
During the period that COVID-19 pandemic outbreak, Chinese universities have adopted a new teaching method combining online and offline and banned students from entering and leaving campus at will in line with the epidemic prevention policy. As a result, college students' learning and life styles have been greatly changed. In order to explore how the epidemic and specific prevention policies have influenced the psychology and behavior of Chinese college students, this study collected the data about college students' subjective well-being, interpersonal relationship and love forgiveness after the epidemic and compared with the data of college students before the epidemic. The study found that before and after the epidemic, college students had obvious changes in their level of interpersonal relationship, subjective well-being and love forgiveness. Relationships among the three variables had changed. Meanwhile, the demographic variables of college students had certain changes in the three questionnaires. College students with and without romantic experience also had significant differences in the three questionnaires. These findings remind relevant departments that it should give greater consideration to the physical and mental health of college students, suggest psychological counselors to change the way of dealing with the intimate relationship of college students, and provide some references for dealing with new outbreaks and formulating the epidemic prevention policies subsequently.